2017
DOI: 10.1177/2055116917730180
|View full text |Cite
|
Sign up to set email alerts
|

Marked paraneoplastic basophilia accompanying eosinophilia in a cat with alimentary T-cell lymphoma

Abstract: Case summaryA 5-year-old male neutered domestic shorthair cat was referred with a history of persistent pyrexia, pica, soft faeces, inappetence, intermittent vomiting, mild-to-moderate granulocytosis and mild hypercalcaemia. No significant improvement was noted after antibiotic and corticosteroid treatment, except that the hypercalcaemia resolved. Physical examination, including thoracic auscultation, and abdominal and peripheral lymph node palpation, were unremarkable. On admission, haematology revealed moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…6 A literature review of veterinary neoplastic and paraneoplastic basophilia revealed seven feline and seven canine cases. The feline cases consisted of three alimentary lymphomas 4,5,7 (two of which were identified as T-cell tumors 5,7 ), chronic myelogenous leukemia (CML), 8 suspected acute leukemia of uncertain lineage, 9 acute myelogenous leukemia (AML) with basophilic differentiation, 10 and acute monoblastic lymphoma with chronic basophilic leukemia. 11 All of these cases, except the AML with basophilic differentiation and the acute monoblastic leukemia with chronic basophilic leukemia, had concurrent eosinophilia, generally of greater magnitude than the basophilia (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…6 A literature review of veterinary neoplastic and paraneoplastic basophilia revealed seven feline and seven canine cases. The feline cases consisted of three alimentary lymphomas 4,5,7 (two of which were identified as T-cell tumors 5,7 ), chronic myelogenous leukemia (CML), 8 suspected acute leukemia of uncertain lineage, 9 acute myelogenous leukemia (AML) with basophilic differentiation, 10 and acute monoblastic lymphoma with chronic basophilic leukemia. 11 All of these cases, except the AML with basophilic differentiation and the acute monoblastic leukemia with chronic basophilic leukemia, had concurrent eosinophilia, generally of greater magnitude than the basophilia (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, among the nine patients with leukemia/MPNs, four were further diagnosed with T-cell lymphoid leukemia. While there are no prior reports in the veterinary literature linking lymphoid leukemia to basophilia, there have been documented cases of T-cell lymphoma in cats resulting in marked paraneoplastic basophilia [ 29 , 30 ]. We also noted the preponderance of T-cell lymphoma in the basophilia group, suggesting a link between T-cell neoplasms and paraneoplastic basophilia.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, basophilia has rarely been reported. Maria Balan et al reported feline basophil prevalence for the first time in 2017, in which case the patient was diagnosed with alimentary T-cell lymphoma ( 2 ). Other reported feline basophilia cases included lymphoma and gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, even though eosinophils and basophils interact with each other at sites of inflammation, basophilia accompanying eosinophilia is extremely rare in cats. Most reported cases are associated with feline alimentary T-cell lymphoma ( 2 ).…”
Section: Introductionmentioning
confidence: 99%